2021
DOI: 10.1177/23743735211008299
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Experiences and Information Needs of Parents Caring for a Child With a Urinary Tract Infection: A Qualitative Study

Abstract: Urinary tract infections (UTIs) are common in children, however, clinical practice variations can leave parents unsure how to care for their child. We aim to develop knowledge tools that provide evidence-based information about pediatric UTIs. To inform tool development, we asked parents to share their experiences and information needs in caring for a child with a UTI. Using qualitative description methods, 16 semistructured interviews were conducted with 18 parents. Parents were recruited through the emergenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 24 publications
(43 reference statements)
0
7
0
Order By: Relevance
“… 13 Catheterisation is often perceived as traumatic by the parents. 14 This might help explain why GPs also prefer using adhesive bags. In a study of semi-structured interviews with parents, parents indicated that they would prefer more guidance on urine collection, 15 and, in the current study, GPs proposed information sheets or video clips as a way to educate parents on urine sampling and storage.…”
Section: Discussionmentioning
confidence: 99%
“… 13 Catheterisation is often perceived as traumatic by the parents. 14 This might help explain why GPs also prefer using adhesive bags. In a study of semi-structured interviews with parents, parents indicated that they would prefer more guidance on urine collection, 15 and, in the current study, GPs proposed information sheets or video clips as a way to educate parents on urine sampling and storage.…”
Section: Discussionmentioning
confidence: 99%
“…Campbell et al found that parents whose children have had at least one UTI could recognize the symptoms and signs of childhood UTIs earlier. 28 In a study of parents’ opinions about diagnosing UTIs in children, Owen et al found that most of the participants believed that health care providers have low childhood UTI awareness levels and do not promptly investigate the possibility of UTIs in children. 22 Practical uncertainties, inadequate knowledge, and financial expenses are health care professionals’ most common obstacles to identifying UTIs.…”
Section: Discussionmentioning
confidence: 99%
“…Parental narratives were informed through semi-structured qualitative interviews (Appendix A) and a systematic review [17][18]. Parents of children who presented to the Stollery Children's Hospital (Edmonton, Canada) with urinary tract infections were invited to participate.…”
Section: Compilation Of Parents' Narrativesmentioning
confidence: 99%
“…Concurrently, a systematic review was conducted to synthesize current evidence about experiences and information needs of parents managing UTI. Results from the systematic review and qualitative interviews are published elsewhere [17][18].…”
Section: Compilation Of Parents' Narrativesmentioning
confidence: 99%